2017
DOI: 10.1021/acsenergylett.7b01096
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Low Overpotential Electroreduction of CO2 to CO on a Supported Gold Catalyst in an Alkaline Flow Electrolyzer

Abstract: Cost competitive electroreduction of CO2 to CO requires electrochemical systems that exhibit partial current density (j CO) exceeding 150 mA cm–2 at cell overpotentials (|ηcell|) less than 1 V. However, achieving such benchmarks remains difficult. Here, we report the electroreduction of CO2 on a supported gold catalyst in an alkaline flow electrolyzer with performance levels close to the economic viability criteria. Onset of CO production occurred at cell and cathode overpotentials of just −0.25 and −0.02 V, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
490
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 444 publications
(504 citation statements)
references
References 53 publications
14
490
0
Order By: Relevance
“…Using Co phthalocyanine as catalysts, we have shown that this dogma can be overcome by applying the complex into a flow cell, generating CO with 94 % selectivity at 165 mA cm −2 current density at basic pH (14) . Such performances approach those obtained with Ag‐ and Au‐based catalytic materials . However, the Co complex, like the above mentioned solid nano‐catalysts, operates at quite large overpotential, in the range of 800 mV at comparably current densities.…”
Section: Methodsmentioning
confidence: 89%
“…Using Co phthalocyanine as catalysts, we have shown that this dogma can be overcome by applying the complex into a flow cell, generating CO with 94 % selectivity at 165 mA cm −2 current density at basic pH (14) . Such performances approach those obtained with Ag‐ and Au‐based catalytic materials . However, the Co complex, like the above mentioned solid nano‐catalysts, operates at quite large overpotential, in the range of 800 mV at comparably current densities.…”
Section: Methodsmentioning
confidence: 89%
“…Prior to application the mixture was sonicated for 20 min. All the anodes had a final loading of 2.01 mg cm −2 …”
Section: Methodsmentioning
confidence: 99%
“…These include the development of structurally complex gas-diffusion electrodes for use in flow cells, [26,27] polymer electrolytes, [28,29] and ionicl iquids [30] that leverage tailorede lectrode-contacting phases to favor high CO 2 availability.I ns ome cases, these approaches rely on interfacial phenomena [31] or involve preparation of membraneelectrode assemblies. These include the development of structurally complex gas-diffusion electrodes for use in flow cells, [26,27] polymer electrolytes, [28,29] and ionicl iquids [30] that leverage tailorede lectrode-contacting phases to favor high CO 2 availability.I ns ome cases, these approaches rely on interfacial phenomena [31] or involve preparation of membraneelectrode assemblies.…”
Section: Introductionmentioning
confidence: 99%